Sanguinarine Inhibits Mono- and Dual-Species Biofilm Formation by Candida albicans and Staphylococcus aureus and Induces Mature Hypha Transition of C. albicans - Weidong Qian; Wenjing Wang; Jianing Zhang; Miao Liu; Yuting Fu; Xiang Li; Ting Wang; Yongdong Li (Pharmaceuticals, 2020)
Previous studies have reported that sanguinarine possesses inhibitory activities against several microorganisms, but its effects on mono- and dual-species biofilms of C. albicans and S. aureus have not been fully elucidated. In this study, we aimed to evaluate the efficacy of sanguinarine for mono- and dual-species biofilms and explore its ability to induce the hypha-to-yeast transition of C. albicans. The results showed that the minimum inhibitory concentration (MIC) and minimum biofilm inhibitory concentration (MBIC90) of sanguinarine against C. albicans and S. aureus mono-species biofilms was 4, and 2 μg/mL, respectively, while the MIC and MBIC90 of sanguinarine against dual-species biofilms was 8, and 4 μg/mL, respectively. The decrease in the levels of matrix component and tolerance to antibiotics of sanguinarine-treated mono- and dual-species biofilms was revealed by confocal laser scanning microscopy combined with fluorescent dyes, and the gatifloxacin diffusion assay, respectively. Meanwhile, sanguinarine at 128 and 256 μg/mL could efficiently eradicate the preformed 24-h biofilms by mono- and dual-species, respectively. Moreover, sanguinarine at 8 μg/mL could result in the transition of C. albicans from the mature hypha form to the unicellular yeast form. Hence, this study provides useful information for the development of new agents to combat mono- and dual-species biofilm-associated infections, caused by C. albicans and S. aureus.